Rule-based knowledge representation for modality learning style in AIWBES - Mokhtar, Rahmah; Mat Zin, Nor Azan; Sheikh Abdullah, Siti Norul Huda (2010)
This paper is emphasizing rule-based knowledge representation in Adaptive Intelligent Web Based Education System (AIWBES).The knowledge was extracted from modality learning style expert based on Dunn & Dunn Model.From the expert point of view, the rules were built up by the researcher.The objective of this paper is to show how knowledge can be represented, producing the rule and replacing questionnaire for learning style prediction.The prototype namely K-Stailo was developed and tested by the researcher.The finding shows that rule-based knowledge representation can be accepted as questionnaire replacement for predicting modality learning style.